Fatwa-fatwa M. Quraish Shihab dalam Bidang Hukum Islam - Mursalim Mursalim; Abu Bakar Madani (LP2M UIN Sultan Aji Muhammad Idris Samarinda, 2013)
This study wanted to see about legal thought of Shihab in one of his book that discuss the issues of Islamic law ,